PARADIGMA EKONOMI KELAUTAN DALAM PERSPEKTIF EKONOMI ISLAM (Reinterpretasi Ayat-ayat Kelautan yang Berdimensi Ekonomi) - Rikmat Ismatullah (JESI (Jurnal Ekonomi Syariah Indonesia), 2011)
The development of Indonesian economic in the future should not merely oriented with land development and ignoring oceanic economic. The greater tendency on the role of oceanic economic in the national development supported to have a great agenda in order to create the policies of oceanic sectors to build the understanding toward Indonesian as a oceanic country. The potencies of Indonesian oceanic can create predominant economic power for this country to face global or international competition. The paradigm of oceanic economic on the Islamic Economic context can be done by discriptioning the reinterpretation of oceanic verses in the economic dimension which can’t be seperated from the life of Indonesian country. In this context we found that Islam has possessed a character as the Ilahiyah system (or resourced with divine law from the God) and universal, (it’s relevant to the whole of times, places, and all aspect of human life), integral, balance, equal, and permanent.Muslim as the majority of the Indonesian people should became the advanced country in the oceanic sector as they have learned it from Qur’anic verses. Al-Qur’an has emphasized Muslim to manage and serve ocean and its properties as the heavent sent (Bless of God). As a matter of fact, its refer to the support of God toward people that they have to take the greaters benefits and advantages, in order to strengthen their faith and to exploit the natural resources especially in the ocean for the welfare and prosperity of human being.Key Word : Al-Qur’an, Oceanic Economic, Islamic Economic